Factors Affecting Acceptance of Teachers in Schools in North of Jeddah to Use Virtual Classrooms in Light of the Unified Theory of Acceptance and Use of Technology (UTAUT) - Alfarani, Leena Ahmad; Almoalim, Bayan Khalid; Albeladi, Ohood Obiedullah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to measure the acceptance of the use of virtual classroom technology in general education by teachers who use it primarily in light of the Unified Theory of Acceptance and Use of Technology (UTAUT), by investigating the factors affecting teachers’ actual use of virtual classroom technology. The study used the quantitative descriptive approach, and the questionnaire was applied on a sample of 304 male teachers and 463 female teachers from the North Educational Office in Jeddah. The study found that the degree of teachers’ acceptance of virtual classes got an overall average (4.02 out of 5) with a high degree of acceptance, and at the level of factors were: the expected effort got the highest average (4.20 out of 5), then the social impact with an average (4.03), then the expected performance with an average (3.94), and the fourth, the available facilities with an average (3.90), and all of them were with a high degree of acceptance. The results of the study also indicated that the four factors positively affect teachers’ use of virtual classrooms with an impact rate of (63.3%); where the expected performance had the highest impact rate (26.5%), then the expected effort with an impact rate of (15.5%), then the social impact with an impact rate of (13.9%), and fourthly, the available facilities with an impact rate of (7.4%). The results of the study also indicated that there were statistically significant differences between the responses of the sample members on the factor of the available facilities in favor of males and between those aged less than 29 years. There are statistically significant differences in the factor of expected performance according to the variable years of experience between those with less than 5 years of experience and the other years of experience. Finally, the study recommended holding training courses for teachers to educate them technically and professionally in the field of teaching using virtual classrooms and improving infrastructure, to ensure the best employment of virtual classroom technology.